Molecular Mechanisms and Current Pharmacotherapy of Peyronie’s Disease: A Review - Zhang, Fuxun; Qin, Feng; Yuan, Jiuhong (Frontiers in Pharmacology, 2021)
Peyronie’s disease (PD) is a localized fibrotic lesion of the penis and have adverse effects on men’s health. In this review, we summarized the molecular mechanisms and pharmacotherapies of PD. Literature search was conducted using PubMed and Cochrane Library during 2001–2020. Although no oral or topical medication demonstrated the efficacy in monotherapy of PD, several intralesional medications have yielded promising results. Currently, the effective strategy in management of PD should be combination modality including but not limited to pharmacotherapy, mechanical therapy and psychotherapy. Meanwhile, the basic research is still necessary to facilitate the development of novel and more reliable treatments. In future, more attention should be focused simultaneously on epigenetic changes, inflammatory cytokines, abnormal wound-healing process, profibrotic and anti-fibrotic factors to provide more options for this refractory disease.